2011
DOI: 10.1111/j.1467-789x.2010.00800.x
|View full text |Cite
|
Sign up to set email alerts
|

Weight gain following treatment with valproic acid: pathogenetic mechanisms and clinical implications

Abstract: SummaryIn the last years, a growing body of literature indicates an association between valproic acid therapy and weight gain. Weight gain during valproate treatment can be observed within the first 3 months of therapy and women seem to be more susceptible than men. The mechanism through which valproic acid may induce a weight gain is still controversial. The scope of this paper is to investigate the possible causal link between treatment and weight gain in epileptic patients. Systematic review of published ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
95
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(106 citation statements)
references
References 121 publications
1
95
0
4
Order By: Relevance
“…Hyperinsulinemia occurred both in VPAtreated patients with epilepsy who gained weight as well as in VPA-treated patients who remained lean (70), and fasting hyperinsulinemia in VPA-treated patients was not associated with increased fasting serum proinsulin or C-peptide concentrations (71). Together, these data do not imply insulin resistance as the cause of hyperinsulinemia; rather, inhibition of insulin metabolism in the liver was suggested to be the cause (reviewed in [68]). It remains to be examined if these side effects of VPA are associated with its HDAC inhibitor function, its effects on the central nervous system or other actions of the drug.…”
Section: Insulin Resistance and Hdac Inhibitionmentioning
confidence: 67%
See 2 more Smart Citations
“…Hyperinsulinemia occurred both in VPAtreated patients with epilepsy who gained weight as well as in VPA-treated patients who remained lean (70), and fasting hyperinsulinemia in VPA-treated patients was not associated with increased fasting serum proinsulin or C-peptide concentrations (71). Together, these data do not imply insulin resistance as the cause of hyperinsulinemia; rather, inhibition of insulin metabolism in the liver was suggested to be the cause (reviewed in [68]). It remains to be examined if these side effects of VPA are associated with its HDAC inhibitor function, its effects on the central nervous system or other actions of the drug.…”
Section: Insulin Resistance and Hdac Inhibitionmentioning
confidence: 67%
“…It remains to be examined if these side effects of VPA are associated with its HDAC inhibitor function, its effects on the central nervous system or other actions of the drug. The fact that VPA is a branched-chain fatty acid may account for these side effects (68). To our knowledge, hyperinsulinemia, insulin resistance and obesity have not been associated with other HDACi in clinical use.…”
Section: Insulin Resistance and Hdac Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the psychiatry clinical setting, it is currently widely used for other indications, such as bipolar disorder, schizophrenia, and schizoaffective disorder as a mood stabilizer, combined with various types of atypical antipsychotics [1,2]. Frequent side effects of valproate treatment include weight gain and/or metabolic effects, although their real incidence or magnitude is unknown and the exact mechanism remains unclear [3][4][5]. Atypical antipsychotics are also associated with metabolic disorders, and vary in their propensity to cause these adverse effects [6].…”
Section: Troductiomentioning
confidence: 99%
“…Valproate treatment has been reported to be associated with obesity [5]. Valproic acid could directly stimulate the secretion of insulin from the pancreatic β cells [3], but it has also been suggested that valproate may interfere with insulin metabolism in the liver, resulting in higher insulin concentrations in peripheral circulation [4].…”
mentioning
confidence: 99%